The Effect of Teaching Table Tennis Using Self-Regulated Learning Model on Self-Esteem - Budiana, Dian; Budiman, Didin; Budiman, Teguh Illahi Widyanto (Universitas Pendidikan Indonesia, 2019)
This study aims to determine whether the self-regulated learning model in table tennis learning can develop self-esteem. This research method uses experiments. The design of this study uses Posttest Only Control Group Design. The population in this study were 80 students of the PGSD Penjas Study Program in the first semester. The sample of this study amounted to 40 people with the taking technique simply random sampling. The instrument used to measure self-esteem uses the Rosenberg instrument self-esteem scale. Data analysis techniques used the independent t-test with SPSS 24 software. Based on the results of the study, the model of self-regulated learning in table tennis game learning influences the self-esteem of FPOK UPI PGSD Penjas study program students in first semester.Â AbstrakPenelitian ini bertujuan untuk mengetahui apakah model self-regulated learning dalam pembelajaran permainan tenis meja dapat mengembangkan self-esteem. Metode penelitian ini menggunakan eksperimen. Desain penelitian ini menggunakan Posttest Only Control Group Design. Populasi dalam penelitian ini adalah mahasiswa Program Studi PGSD Penjas semester pertama yang berjumlah 80 orang. Sampel penelitian ini berjumlah 40 orang dengan teknik pengambilan simple random sampling. Instrumen yang digunakan untuk mengukur self-esteem menggunakan instrument self-esteem scale. Teknik analisis data menggunakan uji independent t-test dengan software SPSS 24. Berdasarkan hasil penelitian dan penghitungan bahwa model self-regulated learning dalam pembelajaran permainan tenis meja berpengaruh terhadap self-esteem mahasiswa program studi PGSD Penjas FPOK UPI